Hadis dan Perannya dalam Tafsir Kontekstual Perspektif Abdullah Saeed - Suryadilaga, Muhammad Alfatih (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
The article highlights Abdullah Saeed’s thought in the light of hadith to promote contextual interpretation of the Qur’an. He emphasizes the significance of Hadith to reach best understanding of Qur’an by putting Hadith as historical reflection of Qur’anic worldview. He argues for five principles that should be implemented in examining Hadith as the source of contextual Qur’anic interpretation. He also highlights the difference of sunnah and Hadith, in which Hadith is perceived as collective cognition not as individual individual perception. Further, he also suggests that understanding Hadith could also be actualized by collective reasoning and human nature (fi?rah) and it should be totally relevant to the Qur’an. Those are the prerequisite of Hadith as the existing source for Qur’anic interpretation. If Hadith doesn’t meet the conditions, although it sounds in terms of chain transmission, the Hadith should be reviewed and even rejected.